"I'll do it my own way!": A young child's appropriation and recontextualization of school literacy practices in out-of-school spaces. (September 2014) - McTavish, Marianne
What do young children do with the literacies they have learned at school? This article reexamines traditional notions of literacy by documenting a second grade child's literacy practices in school and out-of-school contexts. Data collected included field notes, interviews, observations of school and out-of-school literacy practices, and artefacts (such as worksheets, constructions and computer screenshots) from the school, home and community contexts. In analysis, literacy practices were traced to show how meanings travelled across contexts and switched modes. Findings show that the focal child recontextualized school literacies in out-of-school spaces and changed them in flexible, playful and technologically contemporary ways. The study offers new knowledge of how school literacy may impact on some children's out-of-school literacies and recognizes that these out-of-school spaces may serve to prepare children more appropriately for the future.